South Africa Economic Update : Focus on Financial Inclusion - World Bank (Washington, DC, 2014)
Conditions in global financial markets have eased since mid-2012, reflecting improvements in fiscal sustainability and the establishment of mutual support mechanisms in the European Union (EU), even as the global economic recovery remains fragile and susceptible to downside risks. South Africa's growth slowed from 3.5 percent in 2011 to 2.5 percent in 2012, reflecting primarily the sluggish external environment and domestic labor strife. Growth declined in 8 of the 10 major subsectors. Researchers, policymakers, and other financial sector stakeholders are becoming more interested in the transformative power of financial inclusion. In South Africa, expanding access to financial services for individuals and small enterprises could reduce the country's persistent income inequality and stimulate growth. South Africa, as Africa's only G20 member and as one of the BRICS, plays an influential global role, and progress in financial inclusion could thus have an important demonstration effect. While formal financial institutions offer an array of financial services, this Update focuses on formal payments, savings, and credit. Financial inclusion is vital because of the role of financial services in helping individuals and firms withstand income shocks and smooth spending. A well-functioning financial system produces and processes information on investment opportunities and allocates capital based on these assessments; monitors individuals' and firms' performance after allocating capital; facilitates the trading, diversification, and management of risk; mobilizes and pools savings; and eases the exchange of goods, services, and financial instruments.